Differences in extraction methods to antidiarrheal activity in vitro and in vivo in unripe Kayu banana fruit (Musa paradisiaca L. Var. Kayu) - Ningsih, Arista Wahyu; Pratama, Edo; Komariyah, Siti; Astuti, Diah Putri; S. Klau, Ivan Charles; Rahmawati, Dewi (Gaceta Médica de Caracas, 2022)
Introduction: Kayu banana is a fruit found in Lumajang Regency, East Java, with antidiarrheal activity. Phenolic compounds in the unripe Kayu banana fruit have antidiarrheal activity in vivo and in vitro. This study aimed to prove the effectiveness of the extraction method on the phenolic acid content of the unripe Kayu banana fruit (Musa paradisiaca L. var. Kayu) as an antidiarrheal drug and to determine the significant difference between the extraction method on the phenolic acid content and antidiarrheal activity of the unripe Kayu banana fruit (Musa paradisiaca L. var. Kayu).